Design and Optimizing Top Cover Feeding Unit Modular Production System and Pick & Place Station - Emanoelle Napoleon; Agus Halim; Didi Widya Utama; Agustinus Purna Irawan; Jason Waworuntu (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2024)
Modular Production System is a station unit consisting of industrial components in the form of pneumatic and electrical components controlled by a Programmable Logic Controller which is directed for industry-oriented vocational training. In a Modular Production System, there are several types of stations, one of which is the pick and place station which consists of two modules, namely the pick and place module and the conveyor module. This design discusses the optimization of the design of the top cover feeding unit at the pick and place station because the top cover is dislocated every time there is a change in position when the vacuum sucks the top cover. This design optimization is done by redesigning the feeding unit slider. By doing this optimization, it can make the feeding unit accommodate the top cover where it should be and improve the process capability of the system. The results of this optimization are determined based on the process capability values, before optimization the resulting values were 1.0417 for Capabiity Process and 0.77 for the index. Then after design optimization, the values are 3.402 for Capabilty Process and 6.396 for the index and produce a total force of 0.205 N by using a slider feeding unit tilt angle of 14o. This tilt angle was determined as the most optimal angle because it resulted in the least system failure.